2010
DOI: 10.1007/s11199-010-9918-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Mothers and Fathers Who Take Temporary Work Leave

Abstract: The current research investigates perceptions of parents who take temporary leave before returning to work after the birth of a child. This research adds to the current literature by experimentally assessing participants' views of fathers who take leave in addition to mothers who take leave. We used an undergraduate sample (N=167) from a small regional university in the Midwestern United States to assess participants' reactions to scenarios involving a mother or a father who went back to work immediately, took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 39 publications
5
42
1
Order By: Relevance
“…In a similar manner, Brescoll and Uhlmann (2005) found that participants felt less warmly toward an employed mother and a stay-at-home father than their traditional counterparts, believed that the stay-at-home father was a worse parent, and viewed the employed mother as more selfish than the employed father. More recently, Coleman and Franiuk (2011) found that a woman who returned to work immediately after the birth of a child was viewed as less warm than a woman who took a temporary leave or stayed at home, while a man who stayed at home was viewed as less competent than a man who took a temporary leave or remained working (Coleman & Franiuk, 2011).…”
Section: Perceptions Of Deviations From Gendered Family Rolesmentioning
confidence: 99%
“…In a similar manner, Brescoll and Uhlmann (2005) found that participants felt less warmly toward an employed mother and a stay-at-home father than their traditional counterparts, believed that the stay-at-home father was a worse parent, and viewed the employed mother as more selfish than the employed father. More recently, Coleman and Franiuk (2011) found that a woman who returned to work immediately after the birth of a child was viewed as less warm than a woman who took a temporary leave or stayed at home, while a man who stayed at home was viewed as less competent than a man who took a temporary leave or remained working (Coleman & Franiuk, 2011).…”
Section: Perceptions Of Deviations From Gendered Family Rolesmentioning
confidence: 99%
“…In a study conducted more than two decades ago, a stay-at-home father who assumed primary responsibility for child care and housework was evaluated more negatively than a similar stay-at-home mother (Rosenwasser, Gonzales, & Adams, 1985). Nevertheless, these findings were recently replicated in several studies in which a stay-at-home father and an employed mother were evaluated more negatively than a stay-at-home mother and an employed father (Brescoll & Uhlmann, 2005;Coleman & Franiuk, 2011). In Brescoll and Uhlmann (2005) study, participants felt less warmly toward the employed mother and the stay-at-home father than their traditional counterparts, believed that the stay-at-home father was a worse parent, and viewed the employed mother as more selfish than the employed father.…”
Section: Social Judgments Of Gender Norms Violatorsmentioning
confidence: 99%
“…Employers are likely to want employees who stay at work and prefer employees who do not take parental leave. Coleman and Franiuk (2011) also revealed parents who took parental leave were perceived as less successful in their career than working parents. If employers are aware of employees taking parental leave, they are less likely to give those employees crucial responsibilities and are less likely to promote them.…”
Section: Japanese Culture and Fear Of Being Regarded As An Inferior Ementioning
confidence: 99%